Association of gene polymorphisms of pattern‐recognition receptor signaling pathway with the risk and severity of hand, foot, and mouth disease caused by enterovirus 71 in Chinese Han population. Issue 4 (5th January 2018) - Li, Ya‐Ping; Li, Mei; Jia, Xiao‐Li; Deng, Hui‐Ling; Wang, Wen‐Jun; Wu, Feng‐Ping; Wang, Jun; Dang, Shuang‐Suo
Abstract : Hand, foot, and mouth disease (HFMD) caused by enterovirus 71 (EV71) presents with a wide variety of clinical manifestations. Host immune response is a factor that influences disease susceptibility and severity. We investigated the potential association of gene polymorphisms in the pattern recognition receptor (PRR) pathway with the risk and severity of EV71 infection. A total of 180 EV71 HFMD cases (108 severe case; 72 mild cases) were enrolled. A group of 201 sex‐ and age‐matched children was included as a control. All subjects were genotyped for the most common single‐nucleotide polymorphisms (SNPs) in the PRR and the PRR signaling pathway using the SNPscan multiple SNP typing method. Binary logistic regression analysis revealed statistically significant differences in polymorphism of RIG‐1 between patients and controls (rs3739674 G vs C: OR = 1.502, 95%CI: 1.120‐2.014; rs9695310 G vs C: OR = 1.782, 95%CI: 1.312‐2.419). Polymorphisms of RIG‐1 rs3739674 (G vs C: OR = 2.047, 95%CI: 1.307‐3.205) and TLR3 rs5743305 (A vs T: OR = 0.346, 95%CI: 0.212‐0.566) were found to be associated with disease severity. The results indicated that RIG‐1 (rs3739674 and rs9695310) polymorphisms are associated with an increased risk of EV71‐induced HFMD in Chinese children, whereas RIG‐1 rs3739674 and TLR3 rs5743305 polymorphisms are associated with disease severity. These findings support an important role of innate immune mechanism in EV71 infection.